Representasi Problematik Anak Akibat Broken Home Dalam Film Susah Sinyal - Emie Oktavianie; Abbyzar Aggasi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Family has an important role in human life as the first place to learn. However, the Broken Home family has a negative impact on children, such as negative self-concept and difficulties in socializing. The film